Peningkatan Kemampuan Penguasaan Kosakata Kegiatan Sehari-hari Melalui Penerapan Model Pembelajaran Logan Avenue Problem Solving (LAPS) - Masiyem Masiyem (Journal on Education, 2021)
In fact, the education process for elementary school students really gets a challenge when the online learning implementation policy lasts for months. At least some important stages of development for children to be hampered because of social limitations. One of the stages of development that is hampered in children is language. Language is the initial factor that determines children to be able to communicate with their environment. Unfortunately, not a few parents who escape his attention for this one stage of development. As a result, not infrequently, parents will only realize when their child is 3-5 years old. The purpose of this action research is to determine whether there is an increase in vocabulary mastery skills through the application of the Logan Avenue Problem Solving (LAPS) learning model in Class 1-C students of SDN Kendangsari I/276 and to find out how much the increase in vocabulary mastery skills through the application of the learning model Logan Avenue Problem Solving (LAPS) on them. The application of the learning model is carried out in 2 learning cycles, each of which uses 4 hours of lessons. Data was collected by means of documentation, observation, and tests, while the data analysis technique in this study used qualitative data analysis and quantitative data analysis. Based on the results of data analysis and discussion, it can be concluded that there is an increase in vocabulary mastery skills through the application of the Logan Avenue Problem Solving (LAPS) learning model in Class 1-C students of SDN Kendangsari I/276. The increase in vocabulary mastery skills through the application of the Logan Avenue Problem Solving (LAPS) learning model in Class 1-C students of SDN Kendangsari I/276 by 21%.